Brain edema : from molecular mechanisms to clinical practice - Plesnila, Nikolaus (Academic Press is an imprint of Elsevier, 2017)
Brain Edema: From Molecular Mechanisms to Clinical Practice brings together the most widely recognized experts in experimental and clinical brain edema research to review the current knowledge gathered on the molecular and cellular pathophysiology and clinical management of brain edema. This timely book also discusses future directions of research and treatment. Brain edema is an integral and acutely life-threatening part of the pathophysiology of multiple cerebral and non-cerebral disorders, including traumatic brain injury, cerebral ischemia, brain tumors, cardiac arrest, altitude sickness and liver failure. Affecting millions worldwide, research over the past few years has shown that a plethora of complex molecular and cellular mechanisms contribute to this pathological accumulation of water in the brain parenchyma. In parallel, the development of new neuroimaging tools has provided a new way to examine how edema develops longitudinally and in real time, both in pre-clinical models and in patients. Despite intense research over the past few decades, therapeutic options are still limited and sometimes not effective.